The development of Novel, Low Sensitivity, Gas-generating Formulations for Hotwire Ignited Devices - McAteer, Daniel (Cranfield University, 2013)
A novel, low sensitivity, gas-generating composition was developed to replace an existing primary explosive, potassium picrate, for use in a generic squib device. The novel composition was based on energetic materials researched from the open literature. The chosen materials were synthesised or purchased and combined in order to produce formulations which would reproducibly ignite when contacted with a hotwire. The formulations were assessed for their chemical compatibility and homogeneity by small-scale hazard testing, differential scanning calorimetry (DSC) and nuclear magnetic resonance (NMR) spectroscopy. The compositions were test fired within squibs coupled to a pressure bomb and the pressure generation and rise time was measured using a piezoelectric gauge.